Recovery from recurrent depression with mindfulness-based cognitive therapy and antidepressants: a qualitative study with illustrative case studies. Issue 2 (18th February 2020) - Tickell, Alice; Byng, Richard; Crane, Catherine; Gradinger, Felix; Hayes, Rachel; Robson, James; Cardy, Jessica; Weaver, Alice; Morant, Nicola; Kuyken, Willem
Abstract : Objectives: This study aimed to describe the recovery journeys of people with a history of recurrent depression who took part in a psychosocial programme designed to teach skills to prevent depressive relapse (mindfulness-based cognitive therapy (MBCT)), alongside maintenance antidepressant medication (ADM). Design: A qualitative study embedded within a multicentre, single blind, randomised controlled trial (the PREVENT trial). Setting: Primary care urban and rural settings in the UK. Participants: 42 people who participated in the MBCT arm of the parent trial were purposively sampled to represent a range of recovery journeys. Interventions: MBCT involves eight weekly group sessions, with four refresher sessions offered in the year following the end of the programme. It was adapted to offer bespoke support around ADM tapering and discontinuation. Methods: Written feedback and structured in-depth interviews were collected in the 2 years after participants undertook MBCT. Data were analysed using thematic analysis and case studies constructed to illustrate the findings. Results: People with recurrent depression have unique recovery journeys that shape and are shaped by their pharmacological and psychological treatment choices. Their journeys typically include several over-arching themes: (1) beliefs about the causes of depression, both biological and psychosocial; (2) personal agency, including expectations about their role in recovery and treatment; (3) acceptance, both of depression itself and the recovery journey; (4) quality of life; (5) experiences and perspectives on ADM and ADM tapering-discontinuation; and (6) the role of general practitioners, both positive and negative. Conclusions: People with recurrent depression describe unique, complex recovery journeys shaped by their experiences of depression, treatment and interactions with health professionals. Understanding how several themes coalesce for each individual can both support their recovery and treatment choices as well as health professionals in providing more accessible, collaborative, individualised and empowering care. Trial registration number: Clinical trial number ISRCTN26666654 ; post results.